Microbially mediated aluminosilicate formation in acidic anaerobic environments: A cell‐scale chemical perspective. Issue 1 (11th January 2018) - Sánchez‐España, J.; Wang, K.; Falagán, C.; Yusta, I.; Burgos, W. D.
Abstract: Through the use of scanning transmission electron microscopy (STEM) combined with other complementary techniques (SEM, cryo‐TEM, HRTEM, and EELS), we have studied the interaction of microorganisms inhabiting deep anoxic waters of acidic pit lakes with dissolved aluminum, silica, sulfate, and ferrous iron. These elements were close to saturation (Al, SiO2 ) or present at very high concentrations (0.12 m Fe(II), 0.12–0.22 m SO4 2− ) in the studied systems. The anaerobic conditions of these environments allowed investigation of geomicrobial interactions that are difficult to see in oxidized, Fe(III)‐rich environments. Detailed chemical maps and through‐cell line scans suggest both extra‐ and intracellular accumulation of Al, Si, S, and Fe(II) in rod‐like cells and other structures (e.g., spherical particles and bacteriomorphs) of probable microbial origin. The bacterial rods showed external nanometric coatings of adsorbed Fe(II) and Al on the cell surface and cell interiors with significant presence of Al, Si, and S. These microbial cells coexist with spherical particles showing similar configuration (Fe(II) external coatings and [Al, Si, S]‐rich cores). The Al:Si and Al:S ratios and the good Al–Si correlation in the cell interiors suggest the concurrent formation of two amorphous phases, namely a proto‐aluminosilicate with imogolite‐like composition and proto‐hydrobasaluminite. In both cases, the mineralization appears to comprise two stages: a first stage of aluminosilicate and Al‐hydroxysulfate precipitation within the cell or around cellular exudates, and a second stage of SO4 2− and Fe(II) adsorption on surface sites existing on the mineral phases in the case of (SO4 2− ) or on presumed organic molecules [in the case of Fe(II)]. These microbially related solids could have been formed by permineralization and mineral replacement of senescent microbial cells. However, these features could also denote biomineralization by active bacterial cells as a detoxification mechanism, a possibility which should be further explored. We discuss the significance of the observed Al/microbe and Si/microbe interactions and the implications for clay mineral formation at low pH.